2021
DOI: 10.3390/bioengineering8120203
|View full text |Cite
|
Sign up to set email alerts
|

A Wireless Wearable Doppler Ultrasound Detects Changing Stroke Volume: Proof-of-Principle Comparison with Trans-Esophageal Echocardiography during Coronary Bypass Surgery

Abstract: Background: A novel, wireless, ultrasound biosensor that adheres to the neck and measures real-time Doppler of the carotid artery may be a useful functional hemodynamic monitor. A unique experimental set-up during elective coronary artery bypass surgery is described as a means to compare the wearable Doppler to trans-esophageal echocardiography (TEE). Methods: A total of two representative patients were studied at baseline and during Trendelenburg position. Carotid Doppler spectra from the wearable ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A final implication of this novel framework is that emerging technology may help automate ultrasonographic assessments of both preload (e.g., venous Doppler) and stroke volume (e.g., arterial Doppler), simultaneously ( Figure 4 ) [ 97 ]. We have developed a wireless, wearable Doppler ultrasound that concurrently insonates the jugular vein and common carotid artery [ 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. To our knowledge, we have first reported synchronous venous and arterial Doppler during a dynamic assessment, both in a volume-responsive, healthy volunteer and critically ill, septic patient [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…A final implication of this novel framework is that emerging technology may help automate ultrasonographic assessments of both preload (e.g., venous Doppler) and stroke volume (e.g., arterial Doppler), simultaneously ( Figure 4 ) [ 97 ]. We have developed a wireless, wearable Doppler ultrasound that concurrently insonates the jugular vein and common carotid artery [ 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. To our knowledge, we have first reported synchronous venous and arterial Doppler during a dynamic assessment, both in a volume-responsive, healthy volunteer and critically ill, septic patient [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transthoracic comprehensive echocardiography requires views of the complete heart that may not be feasible with a small wearable patch [12]. However, a promising goal for wearable US devices is to provide extended temporal monitoring of patients in and out of the hospital setting, for which it may be sufficient to focus on specific regions of interest or aspects of the heart function relevant to the clinical problem [13]. Wearable US devices may help reduce some sources of variability known to occur in echocardiography measurements [14].…”
Section: A Wearable Us For Cardiovascular Applicationsmentioning
confidence: 99%
“…A wearable US patch attached to the neck was shown to be capable of continuously tracking flow parameters in the carotid artery [13], including continuous qualitative and quantitative tracking of pulsatile flow. A lightweight and wearable US sensor for inspection of blood flow velocities of deep arteries in real time has been developed [19].…”
Section: A Wearable Us For Cardiovascular Applicationsmentioning
confidence: 99%
“…One exciting technology is the wireless and wearable doppler which may be comparable to TEE. For example, Kenny et al showed that a wearable wireless carotid doppler at the common carotid artery is equivalent to TEE during coronary bypass surgeries; it can accurately detect the common carotid artery VTI, and significant changes in SV and aortic VTI after a straight leg raise test [117,118]. Wang et al also described a wearable and flexible ultrasound doppler device similar to an electrocardiogram lead which can monitoring real time blood flow velocities in human arteries [119].…”
Section: Echocardiogram (Echo) For Goal-directed Fluid Therapymentioning
confidence: 99%